Occurrence of virus-induced COPD exacerbations during four seasons. Issue 2 (February 2015) - Djamin, Remco S.; Uzun, Sevim; Snelders, Eveline; Kluytmans, Jan J. W.; Hoogsteden, Henk C.; Aerts, Joachim G. J. V.; Van Der Eerden, Menno M.
Abstract: In this study, we investigated the occurrence of viral infections in acute exacerbations of chronic obstructive pulmonary disease (COPD) during four seasons. Viral infections were detected by the use of real-time reverse transcriptase polymerase chain reaction on pharyngeal swabs. During a 12-month period pharyngeal swabs were obtained in 136 exacerbations of 63 patients. In 35 exacerbations (25.7%) a viral infection was detected. Most viral infections occurred in the winter ( n = 14, 40.0%), followed by summer ( n = 9, 25.7%), autumn ( n = 6, 17.1%), and spring ( n = 6, 17.1%). Rhinovirus was the most frequently isolated virus ( n = 19, 51.4%), followed by respiratory syncytial virus ( n = 6, 16.2%), human metapneumovirus ( n = 5, 13.5%), influenza A ( n = 4, 10.8%), parainfluenza 4 ( n = 2, 5.4%), and parainfluenza 3 ( n = 1, 2.7%). This study showed that virus-induced COPD exacerbations occur in all four seasons with a peak in the winter months. However, the distribution of rhinovirus infections showed a different pattern, with most infections occurring in July.